The meaning of mercury is a study in essence and production (Journal of the College of Basic Education, 2023)
It is no secret to the observer and the contemplative researcher that it is difficult, if not impossible - at least inThe present tense - grasping at what might be called the complexity of meaning and even less than that.Note the meaning and production. Especially since the different studies, old and new, whichI dealt with the follow-up of this issue had varied in approaches and results at the same time.This prompted us to pursue this type of studies in order to be able - even ifOnce again, the matter was marred by caution and failure to reach clear results again.approximation of what is beyond the complexity and what is difficult to contain and report. Therefore, the results were derivedFrom the follow-up analysis of the old and modern theories that followed the movement of meaning in its levelsthe various studies, especially since the study of meaning was and still constitutes a major problem in being a subjectA slippery slope that does not hold one side. From here came different and disparate opinions at the same time. There isOne spoke of the apparent meaning and the other spoke of the hidden meaning. And it didn't stop thereThese limits. Rather, a group of theories tried to hold the individual as the incubator.The first is for the meaning, and this was the case with the historical studies of the vocabulary of the language. while you are attachedSome theories regarding the relationship between the word signified in order to reach the meaning.If modern linguistics is described as having an experimental tendency, as is the case withThe sounds that are subject to clear and tangible tests and analyzes at the same time.Meaning is not subject to this kind of study, as it is not subject to the laws of complexity, even ifRoughly. We may call the meaning - in the light of this pursuit - that it representsAn extended movement that penetrates all the articulations of the language